2017
DOI: 10.1111/jen.12482
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abandonment on syrphid assemblages in mountainous meadows

Abstract: Grasslands are often managed with different intensities in the European Alps. Studies have shown that a medium management can benefit plant and animal biodiversity in these ecosystems. However, in recent decades abandonment of extensively managed meadows is an ongoing global challenge. Syrphids (hoverflies) have been recognized as a threatened group due to environmental drivers, and these managed grasslands provide preferred habitats for them. Yet, at what extent syrphids respond to grassland management strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Similarly, Ponge et al (2013) found endogeic earthworms as K-selected species to be better adapted to disturbances than r-selected anecic species with a higher sensitivity. This may emphasize the marginally higher density of endogeic earthworms in managed sites, which are disturbed by mowing (Ivask et al, 2012). As soil properties between the abandoned and managed meadows were similar, it can be suggested that characteristics of vegetation may have caused the differences in earthworm populations.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Ponge et al (2013) found endogeic earthworms as K-selected species to be better adapted to disturbances than r-selected anecic species with a higher sensitivity. This may emphasize the marginally higher density of endogeic earthworms in managed sites, which are disturbed by mowing (Ivask et al, 2012). As soil properties between the abandoned and managed meadows were similar, it can be suggested that characteristics of vegetation may have caused the differences in earthworm populations.…”
Section: Discussionmentioning
confidence: 94%
“…The managed and abandoned grasslands studied differed greatly in physiognomy and flowering phenology, which might also affect insects (Walcher et al 2017;Hussain et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the ecological consequences of grassland abandonment (Moog et al 2002;Niedrist et al 2009;Walcher et al 2017;Hussain et al 2018). However, little information is available on concurrent changes of soil properties (Köhler et al 2001;Oelmann et al 2017;Zeller et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase sampling efficacy, we assessed the number of hoverfly species and individuals by sweep net sampling and an observation plot method (Hussain et al, 2018). Especially the observation plot method has been shown to increase the number of collected species and individuals (Hussain et al, 2018).…”
Section: Hoverfly Samplingmentioning
confidence: 99%